Effect of Bi3+ Ion Concentration on Physicochemical, Optical and Catalytic Properties of One‐Pot Combustion Synthesized Nanocrystalline Bi‐Doped La2O3. Issue 25 (2nd July 2020) - Gangwar, Bhanu P.; Irusta, Silvia; Sharma, Sudhanshu
Abstract: La2‐2x Bi2x O3 (x=0‐0.04) nanocrystalline powders are synthesized by one‐pot single step solution combustion method. 4 atom% Bi doped La2 O3 reveals the presence of both Bi 3+ and metallic Bi. Temperature programmed reduction (TPR) of La2 O3 and La2−2x Bi2x O3 (x=0.005‐0.04) indicates that the oxygen storage capacity changes with the dopant (Bi) concentration. La2‐2x Bi2x O3 (x=0.04) has less hygroscopic behavior compared to La2 O3 and shown enhanced stability in an open atmosphere. The direct band gap of La2 O3 and La(OH)3 decreases significantly after Bi doping. Further, PL studies of Bi doped compounds show a blue emission at 458 nm due to 3 P1 ‐ 1 S0 transition of the Bi 3+ ion substituted in La2 O3 . Emission intensity is maximum with 0.5 atom percent Bi doping, which decreases gradually with increasing Bi 3+ ion concentration. Bi doping also modifies the catalytic activity of La2 O3, resulting in higher CO oxidation activity than unsubstituted La2 O3 . Abstract : La2 O3, La2 O3 doped with various Bi ions concentrations (La2‐2x Bi2x O3, x (atom%)=0.005‐0.04) and Bi2 O3 have been synthesized by a solution combustion method using oxalyldihydrazide (ODH) as fuel and studied their catalytic and photoluminescence properties. Bi doped La2 O3 compounds show higher activity for CO oxidation reaction when compared to La2 O3 and Bi2 O3 alone. La1.92 Bi0.08 O3 (4 atom% Bi doped La2 O3 ) show higher catalytic activity compared to other chosen catalyst. On the other side, 0.5 atom% Bi doped La2 O3 (La1.99 Bi0.01 O3 ) shows higher emission intensity (shown in the inset of the figure) compared to other Bi doped La2 O3 compounds.